2005
DOI: 10.1108/09534810510589561
|View full text |Cite
|
Sign up to set email alerts
|

The changing nature of work in the age of e‐business

Abstract: Purpose -This paper reviews recent discussions in the information technology (IT) and management literatures in order to consider their implications and to make a series of predictions about organizational life in the coming e-business era. Design/methodology/approach -A wide variety of recent discussions, ranging from comments by political/governmental figures to scholarly reports in the academic literature, are reviewed to consider their implications for the structure and shape of jobs and the job market. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…A work sampling study (Murray, Loos et al, 1998) also showed that the introduction of computer support in the prescription writing process significantly changed the type of work done by hospital based pharmacists. The shifts in work patterns as a result of the internet in health related problem solving over routine procedures has been discussed in other related literature (Landry et al, 2005).…”
Section: Review Of Inventory Models In the Pharmaceutical Industrymentioning
confidence: 99%
“…A work sampling study (Murray, Loos et al, 1998) also showed that the introduction of computer support in the prescription writing process significantly changed the type of work done by hospital based pharmacists. The shifts in work patterns as a result of the internet in health related problem solving over routine procedures has been discussed in other related literature (Landry et al, 2005).…”
Section: Review Of Inventory Models In the Pharmaceutical Industrymentioning
confidence: 99%
“…This could necessitate changes in skills requirements, competencies and lead to mobility of personnel across organizational boundaries (Landry, Mahesh, & Hartman, 2005). The actors within these units will exert differing degrees of social and political influence, perhaps even creating political allegiances to enhance their influence over decision-making.…”
Section: Changing Employment Demographymentioning
confidence: 99%
“…F=57.7 at p=0.000 and t=7.602 which sows HIII is accepted. 18.0% variance by evaluation and Compensation affects the performance measurement of HR in term of efficiency or effect of HR, the value of R=0.180. F=10.65 at p=0.000 and the value of t=0.624.…”
Section: Hiii (Hypothesis Iii): Ict Usage In Training and Develmentioning
confidence: 99%
“…It may be that achievement in ICT usage are exacerbating the difference in employability between the technology-savvy "haves" and "have not's," also known as the "digital divide". [13] Recent studies point up the connections between ICT and social inequalities, their impact on wages, employment structure, and professional skills, vocational training, etc [14]- [18].…”
Section: Introductionmentioning
confidence: 99%